Optimizing Surface Composition and Structure of FeWO4 Photoanodes for Enhanced Water Photooxidation. Issue 8 (29th January 2023) - Ta, Xuan Minh Chau; Nguyen, Thi Kim Anh; Bui, Anh Dinh; Nguyen, Hieu T.; Daiyan, Rahman; Amal, Rose; Tran‐Phu, Thanh; Tricoli, Antonio
Abstract: Photoelectrochemical water splitting is a promising approach to produce green hydrogen using solar energy. A primary bottleneck remains the lack of efficient photoanodes to catalyze the sluggish water photooxidation reaction. Engineering photoabsorbers with a narrow bandgap and suitable band edge can boost the photoelectrochemical performance. Herein, nanostructured iron tungstate (FeWO4 ) photoanodes are engineered directly on a fluorine doped tin oxide glass substrate via a scalable and ultra‐fast flame synthesis route in 13 seconds. Physiochemical, optoelectronic, and electrochemical properties of these photoanodes are systematically investigated. The key roles of charge transport, transfer, and dissolution of W and Fe ions from the FeWO4 matrix within long‐term performance are revealed. Optimal FeWO4 photoanode with a bandgap of 1.82 eV and a FeOOH/NiOOH co‐catalyst coating shows an improved water photooxidation performance, reaching a photocurrent density of 0.23 mA cm −2 at 1.4 V versus reversible hydrogen electrode in 1 m potassium hydroxide. It further demonstrates relatively good photostability, maintaining ≈96% of photocurrent density after 1‐hour continuous photooxidation, albeit some trace of Fe, W and Ni elements dissolution. Insights on the photooxidation performance of nanostructured FeWO4 provide promising directions for the engineering of small band‐gap catalysts for a variety of photoelectrochemical applications. Abstract : Here, nanostructured FeWO4 photoanodes are prepared via an ultrafast flame synthesis route within 13 s. Physiochemical, optoelectronic, and electrochemical properties of these photoanodes as well as influence of cation leaching are systematically investigated and correlated with water photooxidation performance. Optimized photoanodes with optical bandgap of ≈1.82 eV show an improved in photocurrent density in 1 m potassium hydroxide.